Engineering mathematics-IIB(BS-M202) - Ghosh, Dipendra Nath (Aryan Publishing House, 2019)
Engineering mathematics-IIB(BS-M202) / Ghosh, Dipendra Nath. -- Kolkata: Aryan Publishing House, 2019 510 G411v2B No. of Copies : 2